EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN TAXUS SUMATERANA KECAMATAN GUNUNG TUJUH KABUPATEN KERINCI - Frinila Jenisa; iswandi U (JURUSAN GEOGRAFI FIS UNP, 2019)
The objective of this research is to know 1) landform, landform unit and land unit 2) land characteristics of the research area 3) class of land suitability to taxus sumaterana in Gunung Tujuh Subdistrict of Kerinci District. This type of research is descriptive quantitative by using area survey methods, with sampling techniques purposive sampling based on land unit. Class of land suitability obtained by matching of land characteristics with growing condition of taxus sumaterana plants (Matching Method). The land unit consists of two processes the landform from that is process of volcanic origin and process of fluvial origin. The characteristics of the taxus sumaterana, temperature 23oC, precipitation average 1628,63 mm/th, 2,4 month of dry month, drainage moderately well drained - well drained, texture of soil (loam), depth soil >50 cm, soil pH level (6,6-6,8), topography (0-8% - 25-45%). class of land suitability whichis is obtained in the Gunung Tujuh Subdistrict : S1 (very suitable) has a land area 5076,28 hectare (33,91%), N1 (Non suitable) has a land area 9892,31 hectare (66,09%).